2005
DOI: 10.1002/esp.1203
|View full text |Cite
|
Sign up to set email alerts
|

Channel adjustments of the lower Trinity River, Texas, downstream of Livingston Dam

Abstract: Channel cross-sectional changes since construction of Livingston Dam and Lake Livingston in 1968 were studied in the lower Trinity River, Texas, to test theoretical models of channel adjustment, and to determine controls on the spatial extent of channel response. High and average flows were not significantly modified by the dam, but sediment transport is greatly reduced. The study is treated as an opportunistic experiment to examine the effects of a reduction in sediment supply when discharge regime is unchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 32 publications
3
108
0
Order By: Relevance
“…This finding indicates that valley width plays a key role in braided degree, active channel width, and channel activity. In terms of braid index, as long as the background environment has abundant sediment (mainly gravels and sands in this case), steep valley slope, and frequent flood events, the wider valley could provide more space for developing braided channels [23,24] and also main channel shifting [25]. The highest braid index occurs in Z7 in the Zhuoshui River and G3 in the Gaoping River.…”
Section: The Influence Of Valley Width and Hydraulic Construction Upomentioning
confidence: 94%
“…This finding indicates that valley width plays a key role in braided degree, active channel width, and channel activity. In terms of braid index, as long as the background environment has abundant sediment (mainly gravels and sands in this case), steep valley slope, and frequent flood events, the wider valley could provide more space for developing braided channels [23,24] and also main channel shifting [25]. The highest braid index occurs in Z7 in the Zhuoshui River and G3 in the Gaoping River.…”
Section: The Influence Of Valley Width and Hydraulic Construction Upomentioning
confidence: 94%
“…A number of studies deal with the complex response of alluvial river channels due to dam construction (Xu, 1990;Sherrard and Erskine, 1991;Phillips et al, 2005). There are, however, few investigations on alluvial sand-bed rivers with very variable flow regimes and suspended sediment loads which are comparable to the Yellow River (Chien, 1985;Xu, 2001;Hu et al, 2006) (Tables 1 and 2 The exponents b and β show a decreasing trend but f and m an increasing trend.…”
Section: River Channel Adjustment To the Operation Of Damsmentioning
confidence: 99%
“…Petts (1979) suggested that such adjustments vary spatially and change with time in response to the alteration of flow regime, and Xu (1990) presented further detailed discussion on the complexity of downstream temporal responses using evidence from laboratory experiments and field investigations. Phillips et al (2005) found multiple combinations of increase, decrease or no change in width, depth, slope and roughness in response to dam regulation. Although there have been attempts to generalize the hydrogeomorphic effects of impoundment (Brandt, 2000a,b;Petts and Gurnell, 2005), it remains difficult to predict channel adjustment downstream of dams because of differences in dam operation modes since their construction.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations